Pengaruh Literasi Keuangan Syariah Terhadap Keputusan Pembiayaan UMKM Di Labuhanbatu Melalui Akad Syariah - Erni Wahyuni; Tetty Rahmiati Harahap; Mhd. Amin (JOURNAL OF SHARIA ECONOMICS, 2024)
Abstract This study aims to analyze the impact of Islamic financial literacy on financing decisions of micro, small, and medium enterprises (MSMEs) in Labuhanbatu Regency through the understanding of Sharia contracts. A quantitative approach using a survey method was employed to collect data from 112 MSME actors selected through purposive sampling. The research instrument was validated using validity and reliability tests, and data analysis was conducted through multiple linear regression. The results indicate that Islamic financial literacy significantly and positively influences MSME financing decisions, both directly and through the understanding of Sharia contracts. These findings highlight the importance of Islamic financial literacy in enhancing access to and adoption of Sharia-based financing. This study also provides recommendations for local governments and Islamic financial institutions to improve Islamic financial literacy through training and socialization programs to support MSME development and strengthen the Sharia economic ecosystem in Indonesia.